2020
DOI: 10.3389/fneur.2020.529930
|View full text |Cite
|
Sign up to set email alerts
|

Brain Amyloid Burden and Resting-State Functional Connectivity in Late Middle-Aged Hispanics

Abstract: Non-linear relations of brain amyloid beta (Aβ) with task- based functional connectivity (tbFC) measured with functional magnetic resonance imaging (fMRI) have been reported in late middle age. Our objective was to examine the association between brain Aβ and resting-state functional connectivity (rsFC) in late middle-aged adults. Global brain Aβ burden was ascertained with 18 F-Florbetaben Positron Emission Tomography (PET); rsFC was ascertained on 3T Magnetic Resonance Imaging (MRI) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…We did not detect any significant associations between pathological brain burden and changes in RSFC trajectories within the intrinsic brain networks. This observation replicates the previous study ( Köbe et al, 2021 ) and is in part convergent with other reports ( Tahmi et al, 2020 ). Cross-sectional studies have, however, documented RSFC alterations in the setting of Aβ burden or vascular brain injury in non-clinical and clinical cohorts ( Hedden et al, 2009 ; Mormino et al, 2009 ; Elman et al, 2016 ; Schulz et al, 2021 ), with some of the Aβ-related RSFC alterations involving more focal hub regions ( Hedden et al, 2009 ; Mormino et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…We did not detect any significant associations between pathological brain burden and changes in RSFC trajectories within the intrinsic brain networks. This observation replicates the previous study ( Köbe et al, 2021 ) and is in part convergent with other reports ( Tahmi et al, 2020 ). Cross-sectional studies have, however, documented RSFC alterations in the setting of Aβ burden or vascular brain injury in non-clinical and clinical cohorts ( Hedden et al, 2009 ; Mormino et al, 2009 ; Elman et al, 2016 ; Schulz et al, 2021 ), with some of the Aβ-related RSFC alterations involving more focal hub regions ( Hedden et al, 2009 ; Mormino et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…Using the voxelwise approach, another study showed both positive and negative associations [40]. Finally, 2 studies reported a nonsignificant correlation between amyloid PET and FC [41, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Our rs-fMRI processing pipeline combines steps from the FSL toolbox 35 and in-house-developed techniques 36 . To summarize, slice timing correction was applied to the raw rs-fMRI time series to account for the difference in the acquisition delay between slices.…”
Section: Image Preprocessingmentioning
confidence: 99%